2007
DOI: 10.1142/s0217732307024048
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Black Holes in Friedmann–robertson–walker Universe Dominated by Dark Energy

Abstract: We study the existence of black holes in a homogeneous and isotropic expanding FriedmannRobertson-Walker (FRW) universe dominated by dark energy. We show that black holes can exist in such a universe by considering some specific McVittie solutions. Although these solutions violate all three energy conditions, the FRW background does satisfy the weak energy condition.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Of course, they are wrong, because the repulsive force contributed by the quintessence-like dark energy (w > −1) is not strong enough to prevent the formation of the black hole. This point can be seen in [23], where by considering some specific McVittie solutions, Li and Wang showed that black holes can exist in a Friedmann-Robertson-Walker (FRW) universe dominated by dark energy. However, they require that the weak energy condition should be satisfied (although the other three energy conditions can be violated).…”
Section: Introductionmentioning
confidence: 92%
“…Of course, they are wrong, because the repulsive force contributed by the quintessence-like dark energy (w > −1) is not strong enough to prevent the formation of the black hole. This point can be seen in [23], where by considering some specific McVittie solutions, Li and Wang showed that black holes can exist in a Friedmann-Robertson-Walker (FRW) universe dominated by dark energy. However, they require that the weak energy condition should be satisfied (although the other three energy conditions can be violated).…”
Section: Introductionmentioning
confidence: 92%
“…except in the case of a de Sitter "background" withḢ = 0. The apparent horizons of the McVittie geometry have been studied in [102,103,104,82,54]. Rewrite the metric using the areal radius…”
Section: Mcvittie Solutionmentioning
confidence: 99%
“…See for example[23]. There are many conflicting incorrect claims, ranging from assertions that McVittie solutions are geodesically complete, over the suggestions that they cannot be black holes because of exotic spacelike singularities, to the statement that McVittie solutions in any accelerating universes are black holes.…”
mentioning
confidence: 99%